2018
DOI: 10.1101/272989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capturing the onset of PRC2-mediated repressive domain formation

Abstract: SummaryPolycomb repressive complex 2 (PRC2) maintains gene silencing by catalyzing methylation of histone H3 at lysine 27 (H3K27me2/3) within chromatin. By designing a system whereby PRC2-mediated repressive domains were collapsed and then reconstructed in an inducible fashion in vivo, a two-step mechanism of H3K27me2/3 domain formation became evident. First, PRC2 is stably recruited by the actions of JARID2 and MTF2 to a limited number of spatially interacting “nucleation sites”, creating H3K27me3-forming pol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
162
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(179 citation statements)
references
References 66 publications
17
162
0
Order By: Relevance
“…Recent studies reported that PRC2-chromatin interactions are transient, allowing the enzyme to readily translocate on the substrate for efficient spreading of repressive marks (27,34). Our data presented here show that PRC2-nucleosome linkages can also withstand high tensions, exhibiting mechanical stability comparable to the nucleosome itself.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Recent studies reported that PRC2-chromatin interactions are transient, allowing the enzyme to readily translocate on the substrate for efficient spreading of repressive marks (27,34). Our data presented here show that PRC2-nucleosome linkages can also withstand high tensions, exhibiting mechanical stability comparable to the nucleosome itself.…”
Section: Discussionsupporting
confidence: 54%
“…Although direct evidence is still awaited, it can be envisioned that both stable and transient interactions are at work in order to accomplish de novo installation and self-propagation of H3K27me3 modifications ( Figure 6). The strong interactions may be required for PRC2 recruitment to the nucleation sites via either DNA or nucleosome contacts and for the deposition of initial H3K27me3 foci (34,35), presumably with slow kinetics; whereas the weak contacts facilitate efficient spreading by bridging either adjacent or distal nucleosomes. Indeed, we have shown that the mixture of unmodified and modified nucleosomes weakens PRC2 binding to the chromatin, so does the addition of AEBP2.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an indirect consequence of reduced deposition of H3K27me3 levels together with a reduced affinity of PRC2.1 for target genes. Low H3K27me3 levels could reduce EED affinity for its target sites, compromising spreading and establishment of PcG domains Oksuz et al, 2018) . Reduced H3K27me3 deposition further correlated with specific cPRC1 displacement from all repressed target loci (represented by PCGF2 ChIP-seq), in agreement with cPRC1 being dependent on the deposition of this modification through the specific activity of CBX proteins (Bernstein et al, 2006;Cao et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While we now have a good picture of the accessory subunits interacting with PRC2, their precise roles are only partially understood. This might be due to compensatory mechanisms, such that interfering both with PRC2.1 and PRC2.2 is required to inhibit PRC2 recruitment 19 as observed upon loss of SUZ12 20 .…”
Section: Theirmentioning
confidence: 99%